Hadis Sifat Allah: Keunikan Ganjil, Makna dan Tafsir Komprehensif - Ummy Fadillah Barokah; Uswatun Hasanah; Eko Zulfikar (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This article explores the meaning of the hadith that states that Allah is